MORPHOLOGICAL AND PROPERTIES OF PORTLAND-COMPOSITE CEMENTS WITH CLASS C FLY ASH - Andrie Harmaji; A. Fadillah (Universitas Mercu Buana, 2022)
Portland-composite cements (PCC) were prepared with partial substitution of 5 to 25% of class C fly ash, obtained from East Java steam power plant. Properties of the composite cements was evaluated, through the setting time (initial and final) and compressive strength (3, 7, and 28 days) compared with control PCC. Setting time is retarded in Portland-composite cements with higher fly ash content. The retardation is highest in PCC with substitution of 25% fly ash. Lower compressive strength is obtained after 3 and 7 days of curing for PCC with 5-25% fly ash substitution in comparison with control cement, since pozzolanic reaction still did not show its effect. After 28 days, compressive strength was higher than that for control cement because pozzolanic reaction show its effect, highlighted by compressive strength increase of PCC substituted by 5% and 10% fly ash, 16.48 MPa and 16.52 MPa, respectively. This attributed to the differences in the pozzolanic activity of the applied fly ash. The compressive strength increase was explained by Scanning Electron Microscope (SEM), which shows that PCC with substitution of 10% fly ash had more Tobermorite presented compared to control cement.